O internetowych wersjach zapowiedzi dziennikarskich - Wojtak, Maria (Postscriptum Polonistyczne, 2020)
The article presents the main genological determinants of announcements – such determinants result from the specific character of Internet communication (especially hypertextuality). The author of the article exposes common elements characteristic of both Internet announcements and traditional press announcements. She especially emphasizes genological (intertextuality) and discursive (interactive style of communication) conventions. The article also presents different variants of this genre found existing on the Internet. It also discusses the paradoxes of the genre, which are determined by a matrixlike character of websites, but at the same time it changes dynamically in order to both follow the readers’ expectations and continually transgress them.